2017
DOI: 10.1021/acsmedchemlett.7b00125
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Fluorescently Labeled 68Ga-DOTA-TOC Analog for Somatostatin Receptor Targeting

Abstract: Fluorescently labeled imaging agents can identify surgical margins in real-time to help achieve complete resections and minimize the likelihood of local recurrence. However, photon attenuation limits fluorescence-based imaging to superficial lesions or lesions that are a few millimeters beneath the tissue surface. Contrast agents that are dual-labeled with a radionuclide and fluorescent dye can overcome this limitation and combine quantitative, whole-body nuclear imaging with intraoperative fluorescence imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 24 publications
0
38
0
Order By: Relevance
“…Radiolabeling was performed using a cation exchange cartridge as previously described (12). Following Sep-Pak Light C18 (Waters) purification, the product was diluted with PBS and analyzed by radio-HPLC.…”
Section: Labeling Of Mmc(ir800)-toc With 68 Ga 67 Ga and Gamentioning
confidence: 99%
See 3 more Smart Citations
“…Radiolabeling was performed using a cation exchange cartridge as previously described (12). Following Sep-Pak Light C18 (Waters) purification, the product was diluted with PBS and analyzed by radio-HPLC.…”
Section: Labeling Of Mmc(ir800)-toc With 68 Ga 67 Ga and Gamentioning
confidence: 99%
“…Radioactive uptake studies were performed as previously described (12). Briefly, HCT116-SSTR2, NCI-H69, and non-SSTR2-expressing HCT116-WT cells (200,000 cells/well) were incubated with a 10 nmol/L solution of 68 Ga-MMC(IR800)-TOC, 68 Ga-DOTA-TOC, or a mixture of radiotracer with a 100-fold excess of octreotide at 37 C for 1 hour.…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…3B) that could be blocked in the presence of unlabeled octreotide, indicating receptor-mediated binding. The authors then synthesized a second-generation agent using an MMC analog with a modified pendant arm that contained a carboxyl group for stable chelation of 68 Ga (22). In vitro studies confirmed retention of SSTR2binding properties as shown by the ability of the agent to maximally inhibit cyclic adenosine monophosphate formation (EC 50 , 0.066 6 0.012 nM) and stimulate receptor internalization (EC 50 , 48.7 6 9.9 nM), as well as receptor-mediated uptake that was demonstrated by confocal microscopy and quantitative uptake assays.…”
Section: Peptide-based Agentsmentioning
confidence: 99%